A multi-director continuum beam finite element for efficient analysis of multi-layer strand cables. (November 2021) - Kim, Hyo-Jin; Lee, Dong-Hwa; Yoon, Kyungho; Lee, Phill-Seung
Highlights: A nonlinear beam element is proposed for analysis of multi-layer strand cables. Complex helical geometries of the cables including inter-wire motions are considered. The beam element can be used regardless of the number of subordinate helical wires. Its accuracy and efficiency are illustrated through several numerical examples. Abstract: This study presents a multi-director continuum beam finite element developed for efficient analysis of multi-layer strand cables. The beam element is derived from the continuum mechanics based beam formulation incorporating multi-directors and cross-sectional elements to describe the helical geometries of wires that constitute the strand cables. The main advantage of the present continuum beam formulation is that complex geometries of strand cable and inter-wire motions can be addressed in the framework of the beam kinematics regardless of the numbers of layers and subordinate helical wires. This approach enables simple modeling together with efficient analysis, and allows both geometric and material nonlinearities to be considered. In addition to its excellent accuracy, the proposed beam element model requires a significantly reduced number of degrees of freedom compared to conventional three-dimensional solid finite element models for cable analysis. Through several numerical examples, the predictive ability of the proposed beam model is demonstrated.